Manchester Arena Attack: management of paediatric penetrating brain injuries. (2nd January 2021) - Pringle, Catherine; Bailey, Matthew; Bukhari, Shafqat; El-Sayed, Ashraf; Hughes, Stephen; Josan, Vivek; Ramirez, Roberto; Kamaly-Asl, Ian
Abstract: Purpose: The Manchester Arena bombing on 22 May 2017 resulted in 22 deaths and over 160 casualties requiring medical attention. Given the threat of modern- era terrorist attacks in civilian environments, it is important that we are able to anticipate and appropriately manage neurological injuries associated with these events. This article describes our experience of managing paediatric neurosurgical blast injuries, from initial triage and operative management to longer-term considerations. Materials and methods: Case study and literature review. Results: Paediatric traumatic and penetrating brain injury patients often make a good neurological recovery despite low GCS at time of injury; this should be accounted for during triage and operative decision making in major trauma, mass casualty events. Conservative management of retained shrapnel is advocated in view of low long-term infection rates with retained shrapnel and worsened neurological outcome with shrapnel retrieval. All penetrating brain injuries should receive a prolonged course of broad-spectrum antibiotics and undergo long term follow-up imaging to monitor for the development of cerebral abscesses. MRI should never be utilised in penetrating brain injury cases, even in the absence of macroscopically visible fragments, due to the effect of MRI ferromagnetic field torque on shrapnel fragments. Anti-epileptic drugs should only be prescribed for the initial seven days after injury, as continuing beyond this does not incur any benefit in the reduction of long term post-traumatic epilepsy. Conclusion: All receiving neurosurgical units should become familiar with optimum management of these thankfully rare, but complex injuries from their initial presentation to long term follow up considerations. All neurosurgical units should have well-rehearsed local plans to follow in the event of such incidents, ensuring timely deliverance of appropriate neurosurgical care in such extreme settings.